Beneath the Bell Jar: Exploring Esther Greenwood s Mental Health Journey in Sylvia Plath s Seminal Novel - Jennie Posumah; Muhammad Ilham Ali; Fivy A. Andries (English Education Department, 2024)
This study delves into Sylvia Plath s The Bell Jar focusing on the protagonist Esther Greenwood s nuanced portrayal of mental illness Through a qualitative approach the research explores Esther s psychological journey examining her struggles and resilience in the face of mental health challenges The study employs various literary analysis techniques to dissect and interpret the novel s content with the primary data source being Plath s prose itself This approach provides a broader context and theoretical framework for understanding the novel s themes blending literary analysis with psychological and sociological perspectives The study pays particular attention to the depiction of 1950s psychiatric treatments critically examining their inadequacies and limitations Special focus is given to the portrayal of electroconvulsive therapy a controversial treatment that plays a significant role in Esther s experiences Findings underscore the critical importance of empathetic care and robust societal support in addressing mental health challenges By delving into Esther s experiences the research illuminates the profound impact of understanding compassion and appropriate treatment on individuals struggling with mental illness Furthermore this analysis reveals how Plath s work continues to resonate with contemporary readers touching on timeless themes of identity societal expectations and the human psyche The study argues that The Bell Jar serves as a poignant exploration of mental illness and a critique of societal norms and mental health treatment in mid 20th century America This interdisciplinary approach appeals to a broad scholarly audience interested in literature mental health and social history offering insights that bridge multiple fields of study < p>